Functionalized Graphene and Carbon Materials as Additives for Melt‐Extruded Flame Retardant Polypropylene1. Issue 12 (17th April 2013) - Hofmann, Daniel; Wartig, Karen‐Alessa; Thomann, Ralf; Dittrich, Bettina; Schartel, Bernhard; Mülhaupt, Rolf
Abstract Functionalized graphene nanosheets TRGO and MLG 250, prepared from thermally reduced graphite oxide, represent attractive carbon additives for improving the performance of flame retardant polypropylene (PP‐FR). The influence of carbon nanofiller type and content on morphology, thermal, mechanical, and electrical properties as well as the fire behavior of melt‐extruded PP‐FR is investigated. In contrast to conventional nano‐ and micron‐sized carbon fillers such as expanded graphite (EG 40), nano‐scaled carbon black (CB), and multiwall carbon nanotubes (CNT), only TRGO and MLG 250 afford uniform dispersion combined with simultaneously improved stiffness (+80%), electrical conductivity (3 × 10−5 S · cm−1) and enhanced flame retardancy of PP‐FR, as expressed by lower peak heat release rate (−76%).<inline-graphic xlink:href="ark:/27927/pgg3zmns83h" content-type="mame201200433-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />